BSAC Vanguard Series: Behavioural science and antimicrobial resistance. (16th May 2022) - Brazier, Alix; Merriam, Sarah; Halpern, David
Abstract: Antimicrobial resistance could cause 10 million deaths per year by 2050 if no action is taken. While we depend on researchers to find new antimicrobials, reducing the demand for existing ones requires human behaviour change. This article by The Behavioural Insights Team discusses some of the areas with the greatest potential for behavioural interventions to reduce the development of antimicrobial resistance. Three areas are discussed: (i) 'nudging' antimicrobial stewardship (e.g. highlighting comparative over-prescribing was seen to reduce GP antibiotics prescriptions by 3.3%); (ii) promoting good hygiene practices (e.g. placement and salience of hand sanitizer increased hospital visitor compliance from 0.4% to 19.7%); and (iii) leveraging market forces (e.g. front-of-package labelling could increase demand for meat produced with minimal antibiotics, encouraging food production behaviour change).